Experimental assessment of the thermodynamic factor for diffusion in CoCrFeNi and CoCrFeMnNi high entropy alloys. (December 2018) - Vaidya, M.; Mohan Muralikrishna, G.; Divinski, S.V.; Murty, B.S.
Abstract: The present work provides a first experimental assessment of the product of thermodynamic factor ( Φ ) and the cross correlation term ( S ) for high entropy alloys. Following a pseudo-binary approach, the concentration-dependent interdiffusion coefficients are determined for CoCrFeNi and CoCrFeMnNi high-entropy alloys at 1423 K using four different diffusion couples. Combining the data with the measured previously tracer diffusion coefficients, the value of ΦS for the equiatomic compositions is found to be close to unity for CoCrFeNi while a value of 3 to 5 is obtained for CoCrFeMnNi indicating deviations from the ideal solid solution. The interdiffusion coefficients are higher for CoCrFeMnNi substantiating the fact that an increased configurational entropy need not result in decelerated rates of the atomic transport. Graphical abstract: Unlabelled Image